Knowledge and perceptions towards cardiovascular disease prevention among patients with type 2 diabetes mellitus: A review of current assessments and recommendations - Elnaem, Mohamed Hassan; Elrggal, Mahmoud; Nabeel, Syed; Naqvi, Atta Abbas; Hadi, Muhammad Abdul (Bentham Science Publisher, 2020)
Introduction: Patients with type 2 diabetes mellitus (T2DM) are at significantly higher risk of developing cardiovascular disease (CVD). There is scarcity of literature reviews that describes and summarises T2DM patients' knowledge and perception about CVD prevention.